Beyond binary: optical data storage with 0, 1, 2, and 3 in polymer films. Issue 23 (13th April 2017) - Wei, Peiran; Li, Bowen; de Leon, Al; Pentzer, Emily
Abstract : The evergrowing amount of data created and collected is met with the increased need to store this data. By using a quaternary instead of binary code, data storage capabilities are vastly improved. Abstract : The evergrowing amount of data created and collected is met with the increased need to store this data. In compliment to improving data storage capabilities using engineering controls such as decreased pixel size ( i.e., Blu-ray) or 3-D pixels ( i.e., voxels), chemistry-based approaches are required to move beyond current limitations and meet our future needs. Herein, we present a new methodology to optically store data in a quaternary code of 0, 1, 2, 3 in a commodity polymer containing a low loading of two small molecules, and using heat and UV light to write, and read fluorescence output. The as-prepared film is non-fluorescent (0), and can be written through a wooden or metal mask with thermal treatment (1), light treatment (2), or both (3), giving three different colours of fluorescence under UV irradiation. The flexible polymer film remains colourless and transparent under ambient light after patterning, retains the stored data after exfoliation with sandpaper, and can be removed from the substrate and mechanically deformed without detriment to the pattern. This straightforward and scalable system demonstrates the use of simple and robust chemical reactions to improve data storage capabilities and has the potential to exponentially increase information density.